2018
DOI: 10.1021/acs.orglett.8b01409
|View full text |Cite
|
Sign up to set email alerts
|

An NAD(P)H:Quinone Oxidoreductase 1 Responsive and Self-Immolative Prodrug of 5-Fluorouracil for Safe and Effective Cancer Therapy

Abstract: Tripartite prodrug 1, composed of an NAD(P)H:quinone oxidoreductase 1 (NQO1)-responsive trigger group, a self-immolative linker, and the active drug 5-fluorouracil (5-FU), was designed and synthesized for site-specific cancer therapy. Upon bioreductive activation by NQO1, 1 can release the parent drug 5-FU specifically in NQO1-overexpressing cancer cells. This prodrug exerts comparable antitumor activity and a more favorable safety profile compared with 5-FU both in vitro and in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…Development of natural products to new analogues with improved properties is highly desired in the drug discovery process . Targeted prodrug design for anticancer drugs is one of the interesting strategies in drug discovery. Many anticancer natural products are not target specific and might also be quite toxic to normal cells. To lower the toxicity while keeping the therapeutic property of active natural products, proper structure modification serves as an important and useful tool in drug discovery.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Development of natural products to new analogues with improved properties is highly desired in the drug discovery process . Targeted prodrug design for anticancer drugs is one of the interesting strategies in drug discovery. Many anticancer natural products are not target specific and might also be quite toxic to normal cells. To lower the toxicity while keeping the therapeutic property of active natural products, proper structure modification serves as an important and useful tool in drug discovery.…”
mentioning
confidence: 99%
“…Embedment of an additional molecular device, which is cleavable by a specific enzyme expressed predominantly in tumor cells, is a commonly applied method in contemporary drug design and development . A bioreductive prodrug can be designed to target a specific tumor followed by in situ release of the therapeutic drugs with the reductase (NAD­(P)­H:quinone oxidoreductase 1, NQO1) overexpressed in some tumor cells. Fortunately, the reductases are often reported to be overexpressed in a variety of cancer cells, such as breast cancer, ovarian cancer, thyroid cancer, adrenal cancer, and colon cancer. ,− …”
mentioning
confidence: 99%
“…50 Xu et al tested various indolequinone-based prodrugs and found a compound that exhibited antiproliferative activity against both A549 and HT-29 cells. Lastly, well-known anticancer prodrugs, such as methotrexate, 49 5-fluorouracil, 51 camptothecin, 52,53 and SN-38, 54 with the self-immolative linker were synthesized. After the reduction of quinone moiety, the self-immolative linker of the prodrugs was degraded by itself and the free drugs were released.…”
Section: Enzymes For the Cleavage Linker Of Prodrugsmentioning
confidence: 99%
“…Compound 3 was prepared according to the methodology described by Zhang and coworkers. 14 To a solution of compound 2 (0.400 g, 1.60 mmol) and DCC (0.363 g, 1.76 mmol) in CH2Cl2 (10 mL) was added DMAP (0.022 g, 0.16 mmol), stirring at room temperature. After 30 min, propargyl alcohol (3 equivalents) was added and the mixture was stirred overnight.…”
Section: Synthetic Experimentsmentioning
confidence: 99%